Aplikasi Pembelajaran Bahasa Mandarin Menggunakan Flash pada Android - Adrian Dwi Widiartha; Yulia Kendengis; Kristo Radion (Jurnal Infra, 2016)
Mandarin is the dialect of Chinese spoken in the North and Southwest of Republic of China. International bussiness also prefer people who can speak more than one international language, which is other than English, so Mandarin become one of the language that many people search for. So many people in Indonesia who cannot speak Chinese especially children. Children usually not being taught to learn Chinese in school and the parents also cannot teach MandarinThis application helps people learn Chinese. This application have features such as Picture Guessing, Sound Guessing, Arrange the Sentence, Chinese Spelling, and Writing Chinese Character. Picture Guessing teach user about Mandarin using pictures. Sound Guessing teach user about Mandarin using sound. Arrange the Sentence teach user how to arrange Mandarin sentence based on English sentence or arrange English sentence based on Mandarin sentence. Chinese Spelling teach user how to pronounce Mandarin word correctly. Writing Chinese Character teach user how to write Mandarin character based on the word displayed.Through this application user teach user about Mandarin language about pictures and sounds, user can learn how to write Chinese character based on the word displed, user learn how to pronounce Chinese language correctly, user can learn how to arrange Mandarin sentence based on English question or arrange English sentence based on Chinese question